Comparative Study between Platelet-rich Plasma and Platelet-rich Plasma with Hyaluronic Acid in Knee Osteoarthritis Population - Tilakraj Kulandaivel; Prabhu Angamuthu Nagarajan; Girish Muppala; Uganath Subash Boominathan; Rukhaiya Fathima (Journal of Orthopedics and Joint Surgery)
Objective: Innovatively, this study sought to unveil the potential synergy between platelet-rich plasma (PRP) and hyaluronic acid (HA) injections in alleviating osteoarthritis (OA) knee symptoms, contrasting their combined efficacy with PRP treatment alone. Materials and methods: In a pioneering approach, this study delved into the medical records of knee OA patients who underwent either PRP with HA or PRP alone. Assessment criteria encompassed pain scores, functional evaluations, and patient-reported outcomes. With a cohort of 100 individuals, including 50 recipients of PRP alone and 50 of PRP combined with HA, data analysis was conducted to discern the comparative efficacy of these treatment modalities. Results: In our findings, the age range of participants spanned from 40 to 65 years, showcasing a prevalent occurrence of the condition within this demographic, with a mean age of 52.5. Utilizing the Western Ontario and McMaster Universities (WOMAC) OA index, we evaluated the functional outcomes in all 100 cases in the postoperative period. Notably, in the PRP + HA group, 92% (46 cases) displayed excellent outcomes, while 8% (four cases) exhibited good outcomes. Conversely, in the PRP alone group, 70% (35 cases) demonstrated fair outcomes, whereas 30% (15 cases) showed poor outcomes. Employing the Python formula, we calculated a p-value of 0.002, elucidating the significance of our results. Conclusion: In summary, the findings of this comparative study suggest that incorporating HA with PRP may offer enhanced benefits compared to PRP alone in the treatment of OA knee. This combined therapy shows significant potential in relieving pain, restoring joint movements, and elevating the overall quality of life for patients suffering from this condition. The promising results of this study warrant further investigation through larger-scale, long-term prospective studies to validate these outcomes and to determine the optimal therapeutic approach for effectively treating knee OA.